2008
DOI: 10.1007/s00540-008-0616-4
|View full text |Cite
|
Sign up to set email alerts
|

Adhesiolysis and targeted steroid/local anesthetic injection during epiduroscopy alleviates pain and reduces sensory nerve dysfunction in patients with chronic sciatica

Abstract: Purpose. The aim of this study was to evaluate the effect of adhesiolysis followed by the injection of steroid and local anesthetic during epiduroscopy on sensory nerve function, pain and functional disability in patients with chronic sciatica.Methods. Epidural adhesiolysis using epiduroscopy followed by the injection of steroid and local anesthetic were scheduled in 19 patients with chronic sciatica refractory to lumbar epidural block. Sensory nerve function in legs by a series of 2000 (Aβ fibers), 250 (Aδ fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…No significant differences were found between the groups for any of the measures at any time 77 . Observational studies showed good short‐ and long‐term pain relief 78–83 …”
Section: Treatment Optionsmentioning
confidence: 89%
“…No significant differences were found between the groups for any of the measures at any time 77 . Observational studies showed good short‐ and long‐term pain relief 78–83 …”
Section: Treatment Optionsmentioning
confidence: 89%
“…Several smaller prospective studies have shown positive results and a lack of serious complications [57-60]. One study utilized an interlaminar approach and is notable for dural puncture in 4 of 19 patients (21.1%), one of whom required hospitalization [61].…”
Section: Epiduroscopy and Adhesiolysismentioning
confidence: 99%
“…Initially we were pleased to see some patients getting 3 to 4 months of relief and report seeing recovery of footdrops. This philosophy still proves to be true even in studies in 2008 by Sakai et al [44] in which they found that adhesiolysis with catheter-directed steroid and local anesthetic injection during epiduroscopy alleviated pain and reduced sensory nerve dysfunction in patients with chronic sciatica. The evolution of these findings has changed the process into what it is today [45].…”
Section: Discussionmentioning
confidence: 99%